2023
DOI: 10.3389/fphys.2023.1171636
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a neuromuscular training program on physical performance and asymmetries in female soccer

Abstract: Introduction: Women’s football require optimal neuromuscular system development for injury prevention and performance optimization. Standardized neuromuscular training programs have shown promising results in reducing injuries and functional asymmetries, but evidence on their impact on performance is limited.Methods: This research examined the effects of a 10-week neuromuscular training program on physical performance and asymmetries in female football players. Thirty-eight female players from two Spanish Seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
2
5
1
Order By: Relevance
“…In only two studies [43,44], the level of asymmetry observed in horizontal jump tests for adolescent female soccer players was lower than those recorded in the present study. In adult female soccer players, the level of asymmetry found in our study, for vertical and horizontal jump tests, was much higher (two to three times higher) than the findings of other studies [28,29,46] with adult female soccer players.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…In only two studies [43,44], the level of asymmetry observed in horizontal jump tests for adolescent female soccer players was lower than those recorded in the present study. In adult female soccer players, the level of asymmetry found in our study, for vertical and horizontal jump tests, was much higher (two to three times higher) than the findings of other studies [28,29,46] with adult female soccer players.…”
Section: Discussioncontrasting
confidence: 83%
“…Moreover, we suggest examining the correlation of not only vertical but also horizontal jumping asymmetries with the performance of female soccer players, in a systematic way. To conclude, we suggest practitioners implement strength and power training programs [44,46,48], as well as injury prevention protocols (FIFA 11+), balance training and neuromuscular training [49][50][51], aiming to reduce asymmetries in order to minimize the risk of injuries and potentially improve the performances of female soccer players in certain fitness tests.…”
Section: Discussionmentioning
confidence: 99%
“…These athletic situations are typically limited to the team sports environment, given the increased nature of unplanned and reactionary athletic demands present in that environment. The prototypical—and must thoroughly studied 18-20 —setting for neuromuscular training is in the female soccer athlete. However, any sport with a high rate of cruciate ligament injury and potential for contested athletic movements represents an opportunity for neuromuscular training (Table I).…”
Section: Neuromuscular Trainingmentioning
confidence: 99%
“…Implementation of neuromuscular training demonstrates the ability to improve dynamic balance 34,35 , strength 35 , and proprioception 36 in athletic populations. Although the primary intention of neuromuscular training is to protect the athlete from preventable injury, such training may also yield performance benefits 19,33 .…”
Section: Neuromuscular Trainingmentioning
confidence: 99%
“…Previous studies have reported that female soccer players show significantly lower physical fitness levels compared with their male counterparts [ 3 ]. That said, previous studies have also reported that NMT is well-suited to improve performance and reduce injuries in female soccer players [ 3 , 14 , 15 ], such as the FIFA 11 + training program [ 16 ]. Notably, NMT is a multimodal exercise regime that targets core stability, static and dynamic balance, weight transfer, coordination, rapid CoD, and muscle strength and power activities.…”
Section: Introductionmentioning
confidence: 99%